Research on Digital Management Construction of Surveying and Mapping Geographic Information Data Archives (Journal of Global Humanities and Social Sciences, 2023)
In today's era of digitization and informatization, surveying and mapping geographic information data archives are important information assets in the field of geographic information. This paper discusses the digital management construction of mapping geographic information data archives. In terms of key technologies for digitization of digital management archives, the importance of data acquisition and finishing technology, data storage and management technology, and data retrieval and sharing technology is emphasized. At the same time, digitally managing archives also involves issues such as laws and regulations, data compatibility, and data authenticity, the resolution of which is crucial to guaranteeing the feasibility and credibility of digital management. The design and implementation of an archive digital management system is a key step to realizing the digital management of mapping geographic information data archives, which is of positive significance to promoting the digital management construction of mapping geographic information data archives.